Business planning Say Yummy Sempol Ayam - Isnaini Rochmah; Kaniawati, Keni (Universitas Pasundan, 2025)
Food is made to fulfill human needs. The fast and rapid growth due to the increasing need for food cannot be explained by the limitations of human life. From the lifestyle trends of modern people who prioritize cleanliness for health, consumers choose food that is clean, hygienic and in a standard clean from germs that cause disease. Seeing this business opportunity requires a very precise and careful calculation because it will determine how the market attractiveness and competition in the business field. Say Yummy is a business engaged in the culinary field that offers delicious and quality chicken abacus products with attractive packaging.Say Yummy is a culinary business specializing in high-quality chicken abacus products with appealing packaging. This study aims to evaluate the feasibility of Say Yummy from multiple aspects, including business environment, marketing, operations, human resources, and financial viability. The research employs a qualitative descriptive method, utilizing data collection techniques such as observations and surveys. To develop a well-structured business strategy, analytical tools including the Timmons Model, Business Model Canvas (BMC), and SWOT analysis were applied. The findings indicate that while Say Yummy possesses strong internal capabilities, it is not yet fully prepared to counter external threats. The SWOT analysis highlights the strengths and weaknesses of the business, while the Timmons Model and BMC suggest that Say Yummy has significant potential for success. The study underscores the importance of strategic business planning to enhance competitiveness and ensure long-term sustainability.